Mathematical Modeling and Simulation in Mechanics and Dynamic Systems - Scutaru, Maria Luminița; Pruncu, Catalin I. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present book contains the 16 papers accepted and published in the Special Issue "Mathematical Modeling and Simulation in Mechanics and Dynamic Systems" of the MDPI "Mathematics" journal, which cover a wide range of topics connected to the theory and applications of Modeling and Simulation of Dynamic Systems in different field. These topics include, among others, methods to model and simulate mechanical system in real engineering. It is hopped that the book will find interest and be useful for those working in the area of Modeling and Simulation of the Dynamic Systems, as well as for those with the proper mathematical background and willing to become familiar with recent advances in Dynamic Systems, which has nowadays entered almost all sectors of human life and activity.